BARAD, K. (2023). Cuestión de materia. Trans/Materia/realidades y performatividad queer de la naturaleza. Barcelona: Holobionte Ediciones. - Latorre Ruiz, Enrique (Daimon Revista Internacional de Filosofia, 2026)
Reseña de BARAD, K. (2023). Cuestión de materia. Trans/Materia/realidades y performatividad queer de la naturaleza. Barcelona: Holobionte Ediciones.